Strategi Belajar Membaca Teks Arab Berbasis Belajar Mandiri - Fitriani, Laily (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2019)
ABSTRACT Learning to read cannot be separated in a series of metacognitive, cognitive and social mediation strategies. These three types of strategies have contributed to the implementation of learning to read Arabic texts especially for non-Arabic independent learners. This study aims to identify the problems that emerge when reading Arabic texts, what strategies students use and how the strategies can help them read Arabic texts. The method of this research is descriptive qualitative with a case study approach to students of Arabic Language and Literature departement in five and seven semester. Data collection is conducted by observation, interviews and documents, and analyzed qualitatively. The results of the study explained that: 1) The problems faced by students in reading Arabic texts are lack of understanding of new vocabulary / mufrodat, contextual understanding of texts when vocabulary / mufrodat is in a sentence and reading Arabic texts according to the rules of nahwiyah and shorfiyah; 2) Strategies used in reading Arabic texts are metacognitive, cognitive and social mediation strategies; 3) Strategies in the classroom consist of: opening dictionaries, searching for new vocabulary and summarizing the essence of the text. While the strategy outside the class consists of: discussing with friends, reading Arabic texts / writings through magazines, newspapers, books, and the internet, forming study groups with the application of peer tutors, repeating the material that has been studied, and learning to read texts before entering the class. Keywords: Strategy for learning, reading Arabic text, independent learning